Realizing the Witch - Baxstrom, Richard (Fordham University Press, 2016)
Benjamin Christensen's Häxan (The Witch, 1922) stands as a singular film within the history of cinema. Deftly weaving contemporary scientific analysis and powerfully staged historical scenes of satanic initiation, confession under torture, possession, and persecution, Häxan creatively blends spectacle and argument to provoke a humanist re-evaluation of witchcraft in European history as well as the contemporary treatment of female "hysterics" and the mentally ill. In Realizing the Witch, Baxstrom and Meyers show how Häxan opens a window onto wider debates in the 1920s regarding the relationship of film to scientific evidence, the evolving study of religion from historical and anthropological perspectives, and the complex relations between popular culture, artistic expression, and concepts in medicine and psychology. Häxan is a film that travels along the winding path of art and science rather than between the narrow division of "documentary" and "fiction."